1988
DOI: 10.1002/jlb.44.5.367
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Peritoneal Macrophages in the Steady State

Abstract: Resident peritoneal macrophages (M phi) were labeled in situ by intraperitoneal (i.p.) injection of the green fluorescent cell tracking dye PKH-1. After immunofluorescence staining with M phi specific monoclonal antibodies (Mabs) and phycoerythrin (PE) second antibody, the resident M phi were labeled with both the green dye and red Mab label, while recruited M phi were labeled only with the red Mab tag. These populations were distinguished by two-color flow cytometry. PKH-1 labeled resident peritoneal M phi we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 20 publications
5
31
0
Order By: Relevance
“…The ability to accurately identify a cellular population of interest in a heterogeneous biological environment has accelerated progress in transplantation medicine (Chawla et al, 2006;Morimoto et al, 2005;Sugito et al, 2004), cellular biology (Batard et al, 2000;Hasbold et al, 1999) and immunology (Maus et al, 2001;Melnicoff et al, 1988;Rimaniol et al, 2003;Svane et al, 2002). For nearly two decades, researchers have capitalized upon the properties of CFSE and the PKH dyes for a variety of cell tracking applications including the detection of in vivo labeled targets in both migration and functional assays, studies of the interaction of leukocytes with their cognate cellular partners, and also the analysis of isolated cellular subsets; either as an homogenous culture or in a heterogeneous cellular milieu.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to accurately identify a cellular population of interest in a heterogeneous biological environment has accelerated progress in transplantation medicine (Chawla et al, 2006;Morimoto et al, 2005;Sugito et al, 2004), cellular biology (Batard et al, 2000;Hasbold et al, 1999) and immunology (Maus et al, 2001;Melnicoff et al, 1988;Rimaniol et al, 2003;Svane et al, 2002). For nearly two decades, researchers have capitalized upon the properties of CFSE and the PKH dyes for a variety of cell tracking applications including the detection of in vivo labeled targets in both migration and functional assays, studies of the interaction of leukocytes with their cognate cellular partners, and also the analysis of isolated cellular subsets; either as an homogenous culture or in a heterogeneous cellular milieu.…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic permits a labeled cell to be tracked for extended periods of time (Wallace et al, 1993) and can also be exploited for measuring proliferation, due to the halving of fluorescence intensity as daughter cells are spawned. Indeed, the CFSE and PKH dyes have been invaluable tools in the evolution of cellular studies, allowing for the measurement of cytotoxic effector activity (Lee-MacAry et al, 2001;Simmons et al, 2005;Slezak et al, 1989), monitoring cell trafficking in vivo and in vitro (Chawla et al, 2006;Horan et al, 1989;Morimoto et al, 2005;Sugito et al, 2004;Wallace et al, 1993) and studying resident versus recruited cells in the immune response (Clay et al, 2005;Maus et al, 2001;Melnicoff et al, 1988). Perhaps the most common application of such dyes is the detection of differential proliferation responses among lymphocyte subsets.…”
Section: Introductionmentioning
confidence: 98%
“…It is now thought that high doses of irradiation or corticosteroids could have interfered with results from initial studies. Other researchers have reported that tissue-resident macrophages are not replaced by monocytes in the steady state [52,53]. This has been verifi ed for microglia, CNS-resident macrophages, which originate from yolk sac-derived primitive myeloid progenitors and are maintained by self-renewal [54].…”
Section: Origin and Development Of Macrophagesmentioning
confidence: 91%
“…Because the effect of 1 ϫ 10 6 cells was modest, for the primary implantation we used 1 ϫ 10 7 bone marrow-derived cells. Before implantation, the cells were labeled with a fluorescent cell linker, PKH67 (SigmaAldrich) (Melnicoff et al, 1988), to enable tracing the cells in vivo. The PKH67-labeling procedure for adult somatic stem cells has been described previously in detail (Askenasy and Farkas, 2002;Grøgaard et al, 2007).…”
Section: Methodsmentioning
confidence: 99%